Uji Kualitatif Kandungan Asam Pada Kosmetik dan Bahan Pangan Menggunakan FeCL3 - Oileri Tikirik, Wita; Fakhrurosi, Fakhrurosi; Ibrahim, Ibrahim; Mijra, Mijra; Erza Rahma Kartini, Ade; Yunika, Hilma; Ayu Lestari, Nesti (Politeknik Negeri Ketapang, 2023)
This research aims to carry out qualitative tests on the acid content of four different samples, namely MBK Powder, Salicyl Powder, Citric Acid, and Soy Sauce, using FeCl3 as a reagent. This method is used to identify the presence of certain acid compounds in these samples. The samples were tested by adding FeCl3 solution to the sample solution. Color changes that occur are observed and recorded. The observed reactions are considered indicators of the presence of certain acids in the sample. The results of the study showed that MBK powder, salicyl powder and soy sauce showed significant color changes after being reacted with FeCl3. This color change indicates the presence of phenolic compounds, including salicylic acid in these samples. However, in the Citric Acid sample, there was no significant color change, indicating that citric acid does not react typically with FeCl3 in the context of this qualitative test. This research provides an important contribution in understanding the chemical content of various types of samples and shows that qualitative tests using FeCl3 can be an effective method for detecting the presence of phenolic compounds in samples of MBK Powder, Salicyl Powder and Soy Sauce.